1994
DOI: 10.1111/j.1467-9310.1994.tb00876.x
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical framework for the evaluation of university‐industry relationships

Abstract: The purpose of this paper is to build up a theoretical framework to study university‐industry interorganisational relations (U‐1 IOR) and formulate hypotheses which will be tested on empirical data in a future research phase. Then, a taxonomy for university‐industy relationships is proposed. Finally, the problem of evaluating relationships between universities and industries by defining the concept of ‘relationship performance’ is addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
206
0
23

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(232 citation statements)
references
References 54 publications
3
206
0
23
Order By: Relevance
“…As many authors note (Bonaccorsi and Piccaluga, 1994;Faulkner and Senker, 1995;Schartinger et al, 2001), interactions can be classified in relation to their resource deployment, time length, and formalization agreements. Informal contacts did not score as high as expected.…”
Section: Data Set and Basic Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…As many authors note (Bonaccorsi and Piccaluga, 1994;Faulkner and Senker, 1995;Schartinger et al, 2001), interactions can be classified in relation to their resource deployment, time length, and formalization agreements. Informal contacts did not score as high as expected.…”
Section: Data Set and Basic Descriptive Statisticsmentioning
confidence: 99%
“…Nevertheless, if we consider that in the majority of cooperative partnerships, one of the crucial features is the motivation to learn from one's partner, thus acquiring knowledge that in the majority of cases will complement one's own (Gonard, 1999) this result is somewhat worrying. According to the theory of absorptive capacity (Cohen and Levinthal, 1990), in order to be able to absorb the scientific knowledge transferred by universities, firms need to have a strong internal R&D (Fundación Cotec, 1999), but it has also been shown that partnerships with universities cannot replace internal investment in basic R&D (Bonaccorsi and Piccaluga, 1994;Acosta and Modrego, 1998;Ham and Mowery, 1998).…”
Section: Data Set and Basic Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonaccorsi and Piccaluga (1994) Research Council (AHRC) conducts a research project on cultural engagement and KT, and proposes eight channels of KT including performances, exhibitions, consultations, e-engagement, to measure the outcomes from KT in the sphere of cultural activities (AHRC, 2009b). A more recent UK study proposes a conceptual framework grouping three categories of academic entrepreneurial activities (i.e.…”
Section: Knowledge Transfer Activities In Social Sciences and Humanitiesmentioning
confidence: 99%
“…Similarly to Bonaccorsi and Piccaluga (1994), we characterize informality by the absence of any legal agreement of any form underpinning a collaboration between an academic institution (public research organization or university) and a non-academic partner (firms, government agencies, non-profit organizations, etc.). In contrast with previous studies, however, we establish a mutually exclusive differentiation between formal and informal collaborations: we define a collaboration between a researcher and a partner as informal when this has not been formalized at all through any legal instrument of any type or form involving the academic organization.…”
Section: Introductionmentioning
confidence: 99%